AAV8-mediated Atoh1 overexpression induces dose-dependent regeneration of vestibular hair cells in adult mice. (16th March 2021) - Guo, Jing-Ying; He, Lu; Chen, Zhong-Rui; Liu, Ke; Gong, Shu-Sheng; Wang, Guo-Peng
Highlights: AAV8-mediated Atoh1 overexpression induces hair cell and stereocilium regeneration in the damaged utricle of adult mice. AAV8 vectors of a higher titer increases the number of hair cells compared to those of lower titers. Only Atoh1 overexpression in the higher titer group enhances stereocilium regeneration. Abstract: Vestibular hair cells (HCs) are mechanoreceptors for the detection of head movement. Vestibular HCs of adult mammals never completely regenerate after damage, resulting in vestibular dysfunction. Overexpression of Atoh1 is effective for inducing HC regeneration. However, method of clinical feasibility and improvement of regenerative extent are both in need. Here we used an adeno-associated virus (AAV) serotype 8 vector of two different titers to overexpress Atoh1 in the injured utricles of adult mice. One month after virus inoculation, abundant myosin VIIa-positive cells and immature stereocilia were observed. Quantitative analyses revealed that Atoh1 overexpression replenished vestibular HCs in a dose-dependent manner. Vectors of a higher titer increased the number of myosin VIIa-positive cells compared to those of lower titer. Moreover, only Atoh1 overexpression in the higher titer group enhanced stereocilium regeneration, which is an important step in the maturation of regenerated HCs. Although the current treatment failed to initiate functional recovery of the animals, our results prompt further improvements in the recovery of vestibular dysfunction by AAV.